2007
DOI: 10.17744/mehc.29.3.j344651261w357v2
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Online Counseling

Abstract: In this qualitative study, the authors outline the experiences of 5 research participants who engaged in online chat-based counseling sessions. Participants discussed their experiences related to technological barriers, connecting with their counselor, interacting without visual or verbal feedback, receiving counseling in a personal space, and the flow and pace of the online sessions. The authors provide recommendations for the implementation of online counseling, including discussion of the limitations and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 33 publications
5
57
0
1
Order By: Relevance
“…Proponents of online counseling found Internet interventions to be effective for a variety of concerns, specifically for those who might not otherwise have access to mental health services (Barnett, 2005). Likewise, therapeutic relationships were reportedly experienced in the online context, and some clients preferred online counseling to face-to-face counseling (Haberstroh, Duffey, Evans, Gee, & Trepal, 2007). A host of clinical studies revealed that clients benefitted from online interventions.…”
Section: Psychotherapy and Counseling Onlinementioning
confidence: 99%
See 1 more Smart Citation
“…Proponents of online counseling found Internet interventions to be effective for a variety of concerns, specifically for those who might not otherwise have access to mental health services (Barnett, 2005). Likewise, therapeutic relationships were reportedly experienced in the online context, and some clients preferred online counseling to face-to-face counseling (Haberstroh, Duffey, Evans, Gee, & Trepal, 2007). A host of clinical studies revealed that clients benefitted from online interventions.…”
Section: Psychotherapy and Counseling Onlinementioning
confidence: 99%
“…While the practice of online psychotherapy may be burgeoning, technology issues, the absence of nonverbal cues, and limited focus of counseling sessions may be barriers to establishing and maintaining online counseling relationships (Haberstroh et al, 2007). Likewise, in a study of preference, many undergraduate students slightly preferred face-to-face counseling (Rochlen, Beretvas, & Zack, 2004).…”
Section: Psychotherapy and Counseling Onlinementioning
confidence: 99%
“…Haberstroh, Duffey, Evans, Gee, and Trepal (2007) theorize that a lack of typing, writing, or computer skills is a hindrance to TMHT. Outdated technology that creates delays in communication, or not preparing clients for possible interruptions, also increases frustration (Magaletta et al, 2000).…”
Section: Therapeutic Utilitymentioning
confidence: 99%
“…Hanley (2009), for instance, points out that a major gauge of therapeutic eff ectiveness is therapeutic alliance. Researchers continue to discuss whether a strong client-therapist alliance can be formed without face-to-face contact (Fenichel et al, 2002;Haberstroh, Duff ey, Evans, Gee, & Trepal, 2007;Hanley, 2009;Helton, 2003;Leibert et al, 2006;Lovejoy et al, 2009;Reynolds, Stiles, & Grohol, 2006;Shaw & Shaw, 2006). In addition, researchers are including client satisfaction surveys in their studies on Internetbased mental health interventions as another determining factor of online counseling's effi cacy.…”
Section: Evaluating Effi Cacy In Online Counselingmentioning
confidence: 99%
“…In addition, researchers are including client satisfaction surveys in their studies on Internetbased mental health interventions as another determining factor of online counseling's effi cacy. Haberstroh et al (2007), for example, used a phenomenological methodology in exploring the experiences of fi ve individuals who participated in Internet-based synchronous counseling. Participants were graduate students recruited from a counseling program within a large university.…”
Section: Evaluating Effi Cacy In Online Counselingmentioning
confidence: 99%